Effect of différente gonadotrophins on the follicular development and ovulation in guinea pig (Cavia porcellus) - Soares, Jefferson Aparecido Guilén; Barnabe, Valquiria Hvppólito; Visintin, José Antonio; Fituco, Edwiges Maristela; Barnabe, Renato Campanarut; Verreschi, leda Terezinha Nascimento (Brazilian Journal of Veterinary Research and Animal Science, 1996)
Superovulatory response in guinea pigs submitted to various gonadotrophins was studied in 60 females, equally divided in 10 groups with 6 animals each. In a first phase, each one of 6 groups received PMSG, FSH-p in a single dosis, FSH-p in 3 doses, FSH-h, HMG and NaCI 0.9% (control group), respectively. In a second phase, 4 groups received each one, 22 IU FSH-h, 15 IU FSH-h, HMG and NaCI 0.9% (control group), respectively. Three experimental groups of 2nd. phase also received PGF2alfa. Except for the 2 controls, all groups also received HCG. The 3 first groups of 1st phase presented blocked ovulation. The PMSG-treated group showed generalized luteinization of the ovaries, and the others hadearly folicular luteinization with entrapment of ova. In 2nd phase, a group showed an average number of ovulations - considered as normal for the species - and 2 animals had superovulations. It may be concluded that PGF2alfa takes part in the ovulation mechanism of guinea pigs and that it is possible to increase multiple follicular development by using FSH-h + HCG and HMG + HCG associated or not with PGF2alfa.